Assessed Biochar and Moringa oleifera extracts on barley growth and quality in a salty environment (مجلة العلوم الشاملة, 2026)
The field experiment took place at Institute Farm - Tarhuna - Libya, in the winter of 2022–2023 and 2023–2024. The purpose of the research was to investigate how barley (Giza 128) responded to extracts from biochar and Moringa oleifera in terms of growth and quality in salt conditions. Three repetitions of each treatment were used in the randomizing complete block design (RCBD) experiment. The experimental treatments were, control, biochar at 3, 6, and 9%, and moringa at 5, 10, and 15% were used. Vegetative growth (plant height, number of tillers/ plant, leaf area, and total chlorophyll), yield and yield components (spike length, number of spike/m2, number of spikelet/ spike, 1000-grain weight, grain yield, biological yield (ton/ha), and harvest index), and chemical composition (percentages of nitrogen, phosphorus, potassium, protein, and carbohydrates) are all examined. In comparison to the control treatment, which recorded lower values of these traits, the results showed that increasing Moringa oleifera extract up to 15% recorded higher levels of all vegetative growth studied, including plant height, number of tillers/plant, leaf area, and total chlorophyll. This was followed by biochar extract up to 9%. Conversely, spike length, number of spikes/m2, number of spikelets/ spike, 1000-grain weight, grain yield, and biological yield (ton/ha) all showed higher values when Moringa oleifera extract was increased up to 15%, while biochar at 9% showed a higher harvest index when compared to the control treatment, which showed lower values of these traits. Additionally, compared to the control treatment, which recorded lower values of every chemical composition examined, Moringa oleifera extract up to 15% recorded higher values of nitrogen, phosphate, potassium, protein, and carbs percentages, followed by biochar extract up to 9%. The study's findings suggest that biochar and marina leaf extract can boost the growth and yield of cereal forages cultivated under stressful conditions. We advise using biochar and moringa leaf extract in place of costly, environmentally harmful inorganic fertilizers in dry regions where salt stress is prevalent.
Keywords: Barley (Hordeum vulgare L.), biochar, Moringa oleifera extracts, vegetative growth, yield and yield components, chemical composition